Miltirone enhances the chemosensitivity of gastric cancer cells to cisplatin by suppressing the PI3K/AKT signaling pathway - Wang, Yiping; Lv, Hang; Shen, Li; Chen, Zhe (Frontiers in Pharmacology, 2025)
BackgroundGastric cancer (GC) is one of the most common malignant tumors with poor survival. Although cisplatin is a first-line chemotherapy drug for GC, it still has the potential to develop drug resistance and side effects. Miltirone, extracted from Chinese herb Salvia miltiorrhiza Bunge, has been reported to significantly inhibit some types of cancer. However, its effects on GC have not been studied, the possible anti-tumor effects of miltirone in combination with cisplatin in GC patients have not been explored.Materials and methodsHuman GC cell lines AGS, HGC27, MKN45 and MGC803 cells were treated with miltirone and cisplatin individually or combinatorially. Cell proliferation assay, flow cytometric assay, colony formation assay and Western blot were employed to evaluate the cytotoxic effects under these treatments. Wound healing and transwell assays were used to examine the effects of miltirone and/or cisplatin on GC cell migration and invasion. RNA-seq analysis was used to determine miltirone’s potential target genes in AGS cells. GO analysis and molecular docking assay were used to determine the pathways affected by miltirone. Next, we examined changes in the selected pathway proteins. The in vivo animal model was verified the results of the in vitro experiments.ResultsMiltirone inhibited cell growth, migration, and invasion, as well as induced apoptosis in GC cells. In combinatorial treatments, miltirone synergistically enhanced cytotoxicity of cisplatin in GC cells. Moreover, the expression levels of 606 genes appeared to be significantly modulated by miltirone via RNA-seq analyses, and PI3K/AKT signaling pathway was found to refer to miltirone activity. Furthermore, miltirone together with cisplatin treatment significantly reduced the expression levels of p-PI3K, p-Akt, p-mTOR, while the total levels of PI3K and Akt remained unchanged. In addition, compared with the control group, the tumors growth was significantly suppressed in groups treated with the two agents alone or in combination, and even more so in the combination group in vivo.DiscussionMiltirone inhibited the proliferation of GC cells and significantly potentiates the anticancer activities of cisplatin by downregulating the PI3K/AKT signaling pathway. Combination therapy of miltirone and cisplatin represents a novel potential treatment of gastric cancer.